2019
DOI: 10.1021/acs.iecr.9b01349
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aluminum Addition and Surface Moisture Content on the Catalytic Activity of Sulfated Zirconia in n-Butane Isomerization

Abstract: The effects of aluminum addition and surface moisture on the surface-structure properties and catalytic activity of sulfated zirconia were investigated in n-butane isomerization. Adding 4 mol % Al into zirconia support with coprecipitation method greatly improves the catalytic activity. This is attributed to the monolayer coverage of sulfate species and the maximum of Brønsted acid sites, resulting from the strongly stabilized sulfate species on the tetragonal zirconia (t-ZrO2) surface. The in situ DRIFTS inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…Lately, our density functional theory (DFT) calculations showed that the deprotonation energies (DPE) values of Zr─OH on the SZ surface were depended on their surrounding geometry and hydration degree . The DPE values for terminal and bridging Zr─OH groups on a highly dehydrated SZ surface were 1087 and 1206 kJ/mol, which is well in correspondence with the values estimated by lglesia et al (1110‐1165 kJ/mol) .…”
Section: Activation Of Alkane Over Sulfated Zirconiasupporting
confidence: 86%
See 4 more Smart Citations
“…Lately, our density functional theory (DFT) calculations showed that the deprotonation energies (DPE) values of Zr─OH on the SZ surface were depended on their surrounding geometry and hydration degree . The DPE values for terminal and bridging Zr─OH groups on a highly dehydrated SZ surface were 1087 and 1206 kJ/mol, which is well in correspondence with the values estimated by lglesia et al (1110‐1165 kJ/mol) .…”
Section: Activation Of Alkane Over Sulfated Zirconiasupporting
confidence: 86%
“…At high water coverage, however, the adsorption of water molecules, including the chemical and physical adsorbed ones, decreases the strength of acid sites, resulting from the weakened electron‐withdrawing effect of sulfate species. On the other hand, the DFT calculations by our group highlighted that the DPE values of Zr─OH groups tightly depended on the hydration degree of surface . Namely, with the increase of water coverage, the DPE values of Zr─OH groups increased, implying a weakening in the strength of Brønsted acid sites.…”
Section: Determination Of Intrinsic Structure‐reactivity Relationshipmentioning
confidence: 81%
See 3 more Smart Citations